Planning for sustainable tourism development in Wales: An analysis of destination management plans - Sarah Nicholls; Kate Organ; Beth Cummings (Welsh Economic Review (WER), 2021)
Tourism is a vital component of the Welsh economy and the need to incorporate sustainability principles into new and more responsible forms of tourism development is now widely accepted. Sustainability in a tourism context is multi-faceted, involving consideration of the economic, sociocultural and environmental impacts of tourism on all of the people and places impacted by it, including tourism and non-tourism businesses, residents and guests. Planning for sustainable tourism is therefore complex, requiring integration with other relevant planning processes; wide-ranging stakeholder participation; and, an integrative, iterative and strategic approach. This study assessed the extent to which Wales' regional tourism entities have to date incorporated a stakeholder-driven, sustainability-focused mindset into their planning activities. Evaluation of 22 recent destination management plans revealed that there are many opportunities for improvement in the extent to which the desires of the industry, visitors and residents, and the conditions of the local economy, society and environment, are given equal consideration in tourism planning efforts. The need to refocus is especially important in light of Visit Wales' recently articulated new ambition for tourism and the broader aspirations of the Well-being of Future Generations Act.
Keywords: 330; Participation; planning; strategic; sustainable; tourism; Ökotourismus; Tourismuspolitik; Destinationsmanagement; Wales